Number of Leads With Fragmented QRS Predicts Response to Cardiac Resynchronization Therapy. Issue 1 (18th October 2012) - Celikyurt, Umut; Agacdiken, Aysen; Sahin, Tayfun; Al, Neslihan; Kozdag, Guliz; Vural, Ahmet; Ural, Dilek
Abstract Background: Cardiac resynchronization therapy (CRT) is an effective option in the treatment of patients with heart failure (HF) and wide QRS. Fragmented QRS (fQRS) on 12‐lead electrocardiography has been shown to predict cardiac events in several patient populations. However, the relationship between the number of leads with fQRS and response to CRT has not been investigated. Hypothesis: The number of leads with fQRS may predict response to CRT. Methods: One hundred five patients with HF undergoing CRT were prospectively studied. The presence of fQRS was assessed using standardized criteria. Echocardiographic response to CRT was defined by a ≥15% reduction in left ventricular end‐systolic volume at 6 months follow‐up. Results: Seventy‐four patients (71%) had CRT response after 6 months of follow‐up. In multivariate analysis, significant associates of response to CRT were evaluated adjusting for gender, etiology of cardiomyopathy, QRS width, baseline left ventricular ejection fraction, and the number of leads with fQRS. The number of leads with fQRS was the only predictor of response to CRT (odds ratio: 0.61, 95% confidence interval: 0.48‐0.77, P < 0.001). Conclusions: The more leads with fQRS predicts nonresponse to CRT and may help in the selection of CRT candidates. Clin. Cardiol. 2011 DOI: 10.1002/clc.22061 The authors have no funding, financial relationships, or conflicts of interest to disclose.